DragonHeart [videorecording (DVD)] - Cohen, Rob, 1949-; Quaid, Dennis; Connery, Sean; Postlethwaite, Pete; Thewlis, David, 1963-; Christie, Julie, 1941- (Universal Home Video, 1998)
Sean Connery is the voice of Draco the dragon in this tale of a knight dedicated to an ancient creed of honor and his vow to destroy all dragons.